pH-Controlled Cerium Oxide Nanoparticle Inhibition of Both Gram-Positive and Gram-Negative Bacteria Growth - Alpaslan, Ece (Sci Rep, 2017)
Here, the antibacterial activity of dextran-coated nanoceria was examined against Pseudomonas aeruginosa and Staphylococcus epidermidis by varying the dose, the time of treatment, and the pH of the solution. Findings suggested that dextran-coated nanoceria particles were much more effective at killing P. aeruginosa and S. epidermidis at basic pH values (pH = 9) compared to acidic pH values (pH = 6) due to a smaller size and positive surface charge at pH 9. At pH 9, different particle concentrations did cause a delay in the growth of P. aeruginosa, whereas impressively S. epidermidis did not grow at all when treated with a 500 μg/mL nanoceria concentration for 24 hours. For both bacteria, a 2 log reduction and elevated amounts of reactive oxygen species (ROS) generation per colony were observed after 6 hours of treatment with nanoceria at pH 9 compared to untreated controls. After 6 hours of incubation with nanoceria at pH 9, P. aeruginosa showed drastic morphological changes as a result of cellular stress. In summary, this study provides significant evidence for the use of nanoceria (+4) for a wide range of anti-infection applications without resorting to the use of antibiotics, for which bacteria are developing a resistance towards anyway.